Strengthening mechanisms in a high-strength bulk nanostructured Cu–Zn–Al alloy processed via cryomilling and spark plasma sintering - Wen, Haiming; Topping, Troy D.; Isheim, Dieter; Seidman, David N.; Lavernia, Enrique J. (Acta materialia, 2013)
A bulk nanostructured alloy with the nominal composition Cu–30Zn–0.8Al wt.% (commercial designation brass 260) was fabricated by cryomilling of brass powders and subsequent spark plasma sintering (SPS) of the cryomilled powders, yielding a compressive yield strength of 950MPa, which is significantly higher than the yield strength of commercial brass 260 alloys (∼200–400MPa). Transmission electron microscopy investigations revealed that cryomilling results in an average grain diameter of 26nm and a high density of deformation twins. Nearly fully dense bulk samples were obtained after SPS of cryomilled powders, with average grain diameter 110nm. After SPS, 10vol.% of twins is retained with average twin thickness 30nm. Three-dimensional atom-probe tomography studies demonstrate that the distribution of Al is highly inhomogeneous in the sintered bulk samples, and Al-containing precipitates including Al(Cu,Zn)–O–N, Al–O–N and Al–N are distributed in the matrix. The precipitates have an average diameter of 1.7nm and a volume fraction of 0.39%. Quantitative calculations were performed for different strengthening contributions in the sintered bulk samples, including grain boundary, twin boundary, precipitate, dislocation and solid-solution strengthening. Results from the analyses demonstrate that precipitate and grain boundary strengthening are the dominant strengthening mechanisms, and the calculated overall yield strength is in reasonable agreement with the experimentally determined compressive yield strength.